Mainstreaming Conservation Agendas in the Current Socio-Political Development Context - Khatri, Top B (The Initiation, 2010)
Key Words: Conservation, Green sector, GDP, Federalism, Restructuring, Educating and Awaring, Ecological and economic benefits, Liability, Select group of audience, Biopolitics, Positive guidance and conflict. DOI: 10.3126/init.v2i1.2543 The Initiation Vol.2(1) 2008 pp199-201